Bubble‐Propelled Janus Gallium/Zinc Micromotors for the Active Treatment of Bacterial Infections. Issue 16 (9th March 2021) - Lin, Zhihua; Gao, Changyong; Wang, Daolin; He, Qiang
Abstract: We report a bubble‐propelled Janus gallium/zinc (Ga/Zn) micromotor with good biocompatibility and biodegradability for active target treatment of bacteria. The Janus Ga/Zn micromotors are fabricated by asymmetrically coating liquid metal Ga on Zn microparticles and display self‐propulsion in simulated gastroenteric acid (pH 0.5) at a speed of up to 383 μm s −1, propelled by hydrogen bubbles generated by the zinc–acid reaction. This motion of Ga/Zn micromotors is enhanced by the Ga–Zn galvanic effect. The Ga III cations produced from the degradation of Ga/Zn micromotors serve as a built‐in antibiotic agent. The movement improves the diffusion of Ga III and results in a significant increase of the antibacterial efficiency against H. pylori, compared with passive Ga microparticles. Such Ga/Zn micromotors combine the self‐propulsion, good biocompatibility and biodegradability, and Ga‐based antibacterial properties, providing a proof of concept for the active treatment of bacterial infections. Abstract : Janus Ga/Zn micromotors powered by bubbles are presented as an integrated platform with autonomous movement, self‐degradability, and bacteriostatic capacity. The micromotors are applied to the active target treatment of Helicobacter pylori infection.